AKUNTANSI MANAJEMEN STRATEGIS SEBAGAI PENDUKUNG PERENCANAAN ANGGARAN YANG EFEKTIF DAN EFESIEN: KAJIAN LITERATUR SISTEMATIS - Parlindungan, Antonius Immanuel; Surbakti, Lidya Primta (Journal of Applied Accounting And Business, 2025)
This study aims to conduct a systematic literature review (SLR) on the role of strategic management accounting  as a supportive framework for more effective and efficient budget planning. Data were obtained through a comprehensive review of journals discussing key determinants of budget effectiveness, including planning quality, internal control, human resource quality, and the role of technology. The synthesis results demonstrate that sound budget planning and a robust Government Internal Control System (SPIP) fundamentally and positively influence budget realization, which then serves as a significant mediating variable toward financial accountability. Strategic management accounting contributes by providing essential analytical tools and perspectives, enabling public organizations to shift their focus from mere regulatory compliance (input) toward achieving cost efficiency and performance orientation (outcome) through the principles of performance-based budgeting. Furthermore, the adoption of digital budgeting through information systems like SIPD has been proven to enhance data accuracy and transparency in the planning process. Nevertheless, the effectiveness of budget planning still faces challenges in the form of fiscal stress, which threatens the sustainability of long-term capital budgeting, and structural interoperability issues between e-planning and e-budgeting systems. This review affirms that the integration of strategic management accounting, supported by improved human resource competence and synchronized digital systems, is a crucial step in elevating overall budget planning quality.